Reviewer Acknowledgements for Environmental Management and Sustainable Development, Vol. 10 No. 2 - Young, Jenny (Environmental Management and Sustainable Development, 2021)
Environmental Management and Sustainable Development (EMSD) would like to thank the following reviewers for reviewing manuscripts from February 1, 2021, to May 1, 2021. Their comments and suggestions were of great help to the authors in improving the quality of their papers. Many authors, regardless of whether EMSD publishes their work, appreciate the helpful feedback provided by the reviewers. Macrothink Institute appreciates the following reviewers’ rigorous and conscientious efforts for this journal. Each of the reviewers listed below returned at least one review during this period. Adriano Magliocco, University of Genoa, Italy Christiane do Nascimento Monte, Universidade Federal Fluminense, Brazil Daniel Garraín, Public Research Center for Energy, Environment and Technology, Spain Elham Mohamed, National Research Centre, Egypt Farhaoui Mohamed, National Office of Electricity and Drinking Water, Morocco Gandhi Escajadillo Toledo, Pontifical Catholic University of Peru, Peru Giacomo Chiesa, Politecnico di Torino, Italy Hayssam Mohamed Ali, King Saud University, Egypt Hebin Lin, International Environmental Management Services Ltd (IEMS), USA João Fernando Pereira Gomes, Instituto Superior de Engenharia de Lisboa, Portuguese Khan R. Rahaman, Khulna University, Bangladesh Mona M. Amin Abdel-Fatah, National Research Center in Egypt, Egypt Pankaj Maheshwari, College of Engineering, University of Nevada, Las Vegas, USA Tateda Masafumi, Toyama Prefectural University, Japan